2022
DOI: 10.1136/bmjoq-2022-002003
|View full text |Cite
|
Sign up to set email alerts
|

Improving ICSI success rates following root cause analysis and use of system behaviour charts: the devil is in the detail!

Abstract: A fertility clinic observed a reduction in its fresh intracytoplasmic sperm injection (ICSI) implantation rate key performance indicator (KPI) below benchmark threshold which was further monitored but did not improve. The clinic had been performing ICSI successfully for >16 years with good ICSI implantation rates meeting benchmark level. A root cause analysis (RCA) was conducted, including the input from an external observer, reviewing all systems and processes. A bundle of recommended changes was implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Besides, a project for improving the quality of ICSI to increase its success rate was recently implemented. 160 The authors of this article found that the transplantation rate in ICSI at a certain infertility treatment clinic was below the key performance indicator and did not improve thereafter. Therefore, they implemented a quality‐improvement project and reportedly made a series of changes to improve the transplantation rate in ICSI.…”
Section: New Icsi Attempts and Technical Scrutinymentioning
confidence: 93%
“…Besides, a project for improving the quality of ICSI to increase its success rate was recently implemented. 160 The authors of this article found that the transplantation rate in ICSI at a certain infertility treatment clinic was below the key performance indicator and did not improve thereafter. Therefore, they implemented a quality‐improvement project and reportedly made a series of changes to improve the transplantation rate in ICSI.…”
Section: New Icsi Attempts and Technical Scrutinymentioning
confidence: 93%